Pola Alih Tutur dalam Webseries berjudul ‘SORE-Istri dari Masa Depan’ - Abiyan Fitri Maulana; Mohamad Syahril Rhomadon; Merlina Guspita (Jurnal Bahasa dan Sastra, 2023)
This study examines the patterns of speech transfer in the YouTube series "SORE-Istri dari Masa Depan," produced by the Tropicana Slim channel. The primary objective of this research is to comprehensively identify and describe the diverse modalities of speech transfer embedded within the series' dialogues. A qualitative-descriptive approach incorporating non-involved observation technique for data collection was employed. The analyzed data comprised conversation exchanges between characters within the series. Speech transfer analysis was guided by the theoretical framework of acquiring, stealing, seizing, creating, and continuing. The findings revealed the presence of all five speech transfer patterns, excluding the replacing speech pattern. This discovery significantly contributes to the understanding of the variation of speech transfer patterns in the context of serial dialog, with potential implications for linguistic and popular culture studies.